Targeting the Crimean-Congo haemorrhagic fever virus with natural compounds: an in silico study - Hashim, Hayder Obayes; Makki Al-Hindy, Hayder Abdul-Amir; Raed Razzaq, Mohammed; Badr, Sura Hayder; Ali, Zahraa Ahmed; Abdulwahid, Tabarek Raed (Pharmakeftiki, 2025)
The Crimean-Congo haemorrhagic fever virus (CCHFV) is a highly transmissible pathogen capable of inducing severe haemorrhagic manifestations with high fatality rates. This study has aimed at demonstrating a virtual screening workflow and compound selection strategy to evaluate the potential of natural compounds to inhibit CCHFV through its ovarian tumor domain protease (vOTU); a key mediator of immune evasion. From a curated library of 5,749 natural compounds, five candidates met the selection criteria. Among these, 1,3,6-trigalloyl glucose exhibited the highest binding affinity (XP GScore: -9.351 kcal/mol) and geometric stability, as evidenced by a root mean square deviation (RMSD) of <4.5 Å in molecular dynamics simulations. The second most promising compound, 2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-4-oxo-4H-chromen-3-yl 6-O-(6-deoxy-α-L-gulopyranosyl)-β-D-talopyranoside, demonstrated an XP GScore of -7.909 kcal/mol and an RMSD <2.8 Å. These findings suggest that the identified natural compounds may serve as promising antiviral candidates against CCHFV. Further experimental validation is warranted in order to assess their therapeutic potential. Overall, this study underscores the utility of in silico approaches for the identification of novel antiviral agents derived from natural sources.